Kualifikasi Tenaga Kerja Pada Berbagai Klasifikasi Penyelenggaraan Makanan Massal: Tinjauan Berdasarkan Jumlah Konsumen dan Jenis Menu Yang Disajikan - Nur Rahman; Bachyar Bakri (JURNAL INFO KESEHATAN, 2019)
Labor requirements on the food services can be influenced by the type or the type of menu that is served (menu option or standard menu/set), a number of customers served and characteristics, manner of presentation/foodservice and food processing techniques used. The purpose of this study was to analyze the manpower needs of consumers in terms of number and type of menu served in various classifications of food services. This research is a descriptive exploratory descriptive design. The sampling technique research conducted by purposive sampling method, research carried out for 3 (three) months, starting month from July to October 2015. The variables studied were the number of consumers served, number of workers, a qualified workforce, and the type/types of menu that are used. Data were collected by interview with the manager of the implementation of food assisted questionnaires and direct observations on the foodservice. The data is processed and analyzed descriptively, then presented in tabular form. The result showed that the number and qualification of labor needed in the various classifications of food services, most are high school or vocational school graduates, with the main task generally is a food processing power. Special hospital for the provision of food needed nutritionist with 1:57 lowest and the highest ratio of 1: 400. At food services in addition to the hospital, the need is determined by the number of consumers served and depending on the extent of the physical building of the institution. Kind/type menus presented on the hospital food service, boarding, catering, social institutions, and school children are the menu cycle. While the implementation of commercial food using the options menu (selected menu). Given the number and qualification of manpower needs of each institution organizing food can not be used as a standard, it is necessary assessments using calculations based on the analysis of the workload of each field of labor tasks.